In vitro propagation of mature trees of Sorbus aucuparia L. and field performance of micropropagated trees - V. Chalupa (Journal of Forest Science, 2002)
The influence of tree age, explant source and genotype on micropropagation of mature trees of Sorbus aucuparia has been investigated. Experiments demonstrated the feasibility to use juvenile parts of mature trees for in vitro propagation of selected genotypes. Explants from lower branches and from epicormic shoots of mature trees exhibited high multiplication coefficients of microshoots cultured on modified MS agar nutrient medium supplemented with cytokinin (BA, TDZ) and auxin (IBA). Microshoots produced from juvenile parts of mature trees exhibited good rooting response and produced plants were well adapted to grow in forest soils. The survival of micropropagated trees planted in experimental plots was high and losses during winter were low. Height and diameter increments of micropropagated trees originated from juvenile parts of mature trees were considerable and their dimensions after five years of growth were comparable with the dimensions of trees originated from seeds.